Late Transition Metal Compounds with 1, 1′‐Bis(phosphino)ferrocene Ligands. Issue 2 (25th October 2016) - Hartlaub, Sage F.; Lauricella, Nicole K.; Ryczek, Catherine N.; Furneaux, Aliza G.; Melton, Jon D.; Piro, Nicholas A.; Kassel, W. S.; Nataro, Chip
Abstract : The syntheses of several new zinc compounds with 1, 1′‐bis(phosphino)ferrocene ligands and their phosphine chalcogenide derivatives are reported. The X‐ray crystal structures of [Zn(dppdtbpf)Cl2 ] [dppdtbpf = 1‐diphenylphosphino‐1′‐(di‐ tert ‐butylphosphino)ferrocene], [Zn(dippfO2 )Cl2 ] [dippf = 1, 1′‐bis(diisopropylphosphino)ferrocene], [Zn(dtbpfO2 )Cl2 ] [dtbpf = 1, 1′‐bis(di‐ tert ‐butylphosphino)ferrocene], and [Zn(4 S)Cl2 ] (4 = dppdtbpf) were determined. The oxidative electrochemistry of the zinc compounds was examined and typically produced irreversible oxidations. The reactions of [(AuCl)2 (PP)] [PP = 1, 1′‐bis(diphenylphosphino)ferrocene (dppf), dtbpf, or dppdtbpf] with [N( p ‐C6 H4 Br)3 ][B(C6 F5 )4 ] result in the loss of a chlorido ligand to form [Au2 (µ‐Cl)(PP)][B(C6 F5 )4 ]. The structures of [(AuCl)2 (dtbpf)] and [Au2 (µ‐Cl)(dtbpf)][B(C6 F5 )4 ] were determined, and [Au2 (µ‐Cl)(dtbpf)] + displays a weak Au–Au interaction that is not present in [(AuCl)2 (dtbpf)]. The oxidative electrochemistry of [Au2 (µ‐Cl)(PP)] + displays two reversible waves, the first of which occurs at a potential similar to those of the corresponding [(AuCl)2 (PP)] species. Abstract : Zinc compounds containing 1, 1′‐bis(phosphino)ferrocene ligands and several phosphine chalcogenide derivatives are prepared, and most are characterized by X‐ray crystallography. The removal of a chlorido ligand from [(AuCl)2 {1, 1′‐bis(phosphino)ferrocene}] results in the formation of [Au2 (µ‐Cl){1, 1′‐bis(phosphino)ferrocene}] + species, which contain weak Au–Au interactions.